Determination of the added value of kades coffee agroindustry product using the hayami method (case study of MSME’s Agal Deta, Sumbawa Besar District) - Rizaldi, Lalu Heri; Madani, Hamzah Rizqi; Ariskanopitasari, Ariskanopitasari; Mikhratunnisa, Mikhratunnisa (Universitas Muhammadiyah Mataram, 2023)
Coffee is an agro-industrial product commodity that has the potential to be developed, because it can be processed into ground coffee products with various flavors and can last a long time. This study aims to analyze the added value of Kades Coffee Agro-industry products in the MSME’s of Agal Deta which located in Marente Village, Alas District, Sumbawa Besar Regency using the Hayami method. The variables used in this method include input output and prices, revenues and profits, and margins. The results of the analysis of the added value of Kades coffee on the output, input and price variables obtained a conversion factor value of 5 kg/production cycle and a labor efficiency of 0.32 HOK/kg. The revenue and profit variables obtain of added value ratio of 76%, a profit level of 83% and an added value of 95,000 IDR. The margin variable gains a profit of 79% with a margin value of 100,000 IDR. The added value of Kades coffee is included in the profitable business category because it gets a added value ratio of above 40%.